Guilt norms regarding historical violence and implications for intergroup relations in France. (January 2018) - Bonnot, Virginie; Krauth-Gruber, Silvia
Abstract: The present study examines how guilt norms regarding past French colonization in Algeria (one of the North African countries referred to as the Maghreb) are linked to collective guilt and other negative group-based emotions, contemporary intergroup attitudes towards immigrants of the former colonies and their descendants (French Maghrebians), and conciliatory behaviors. Seventy French students, with no past family relationships regarding colonization, answered questions measuring both injunctive and descriptive collective guilt norms for the in-group (what French people should feel and actually feel, respectively), as well as the injunctive guilt norms for two out-groups (what English and Turkish people should feel for their own country's violent past). Results revealed strong injunctive and descriptive no-remorse norms for the in-group as well as an injunctive no-remorse norm for the English out-group. The Turkish out-group, on the contrary, was expected to feel particularly guilty for the Armenian genocide. Both in-group norms were linked to less expression of all negative group-based emotions and to less intention to compensate. Moreover, the injunctive, but not the descriptive, no-remorse norm for the in-group predicted more prejudiced attitudes and less signing a petition asking for apologies. Unexpectedly, the injunctive pro-remorse norm for the Turkish out-group predicted less intention to compensate, more prejudiced attitudes, and less conciliatory behavior. These results show that emotional norms in response to the colonial past of one's nation may prevent people from feeling any negative group-based emotions and may contribute to upholding negative relationships with compatriots of Maghrebian (i.e., North African) descendants.